Lepkosprężysty Pręt Kołowy na Podłożu o Dwukierunkowej Charakterystyce Lepkosprężystej - Skalmierski, B.; Tylikowski, A. (Engineering Transactions, 1966)
The foundation considered is assumed to respond to radial and tangential displacement (two characteristic constants). The problem is considered in two aspects: quasi-static and dynamic in which inertia forces are taken into consideration. The point of departure are the equilibrium equations of a bar subject to bending (...) where W and V are the displacements of the bar and q and p - the loads in the radial and tangential direction, respectively. The results are obtained on the ground of the elastic-viscoelastic analogy. Green's function of the problem is obtained enabling the obtainment of the displacements for any loads by means of the equations (...) As a separate problem is considered a full bar loaded by radial and tangential forces travelling along the periphery with velocity V. Such a state of load is encountered in the operation of driving wheels of any kind. The Voigt model is assumed for detailed analysis. The influence of the radial load on the Iongitudinal strain is rejected. (...)